CUSTOMER BONDING: STRATEGI UNTUK MEMPERTAHANKAN PELANGGAN (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2004)
The changes in marketplace and the challenges facing corporate marketing whereby customers will need to be convinced about product or services and corporate credibility. This shift request marketer move towards maintained the customer by doing the loyalty program. Are was a strategy, named as Customer Bonding Customer bonding is a new strategy to maintain customer and defend relationship with the customer who have had. There were some steps in customer bonding that could imply, that is :awareness bonding identity bonding relationship bonding community bonding and advocacy bonding. The purpose of this research is to prove the relationship between customer bonding and customer loyalty. This purpose of this research is also to explore about the implication of customer bonding strategy and how effective this strategy to be communicate to the customer This research chose Mc Donald Surabaya, as a place where this research was done. Samples of this research are Mc Donald customer's which are chosen by purposive sampling method This research determines samples criteria, that is the samples must be an individual customers and had visited Mc Donald once or more a month. Hypothesis are tested by descriptive statistics for explore the implication of customer bonding strategy at Mc Donald Surabaya. And this research use Rank Order Spearman Correlation to prove the effectiveness of customer bonding to customer loyalty., using program software SPSS version 10.00. Inferential statistics is used to test hypothesis by t- test at a = 0,05 level of signfcance at two tailed test. he result of this research confirms that hypothesis of this research are accepted Mc Donalds Surabaya have implied customer bonding strategy during all steps that were: awareness bonding identity bonding relationship bonding community bonding, and advocacy bonding. All the steps are effective enough to communicate to the customers. And the customer bonding looked effective to maintenance customer loyalty.